Analysis of Absorbance Value of Flavonoid Level in Brotowali Stem Extract Using UV-VIS Spectrophotometer - Yunike Kurnia Unda; Elisabet Sa Wulo; Suparno (Jurnal Penelitian Pendidikan IPA, 2025)
Flavonoids are polyphenolic secondary metabolites with various biological activities, including antioxidant and anti-inflammatory effects. This study aimed to determine the total flavonoid content in Tinospora crispa (brotowali) stem extract using the AlCl₃ colorimetric method and UV-Vis spectrophotometry. The brotowali stems were extracted using a decoction method with distilled water as the solvent. The formation of a yellow complex between flavonoids and AlCl₃ was measured at a wavelength of 435 nm using a UV-Vis spectrophotometer. A standard calibration curve was prepared using quercetin as the reference compound. The absorbance values of the sample were compared against the quercetin standard curve to determine the flavonoid concentration, expressed as mg quercetin equivalent (QE) per 100 g of extract. The total flavonoid content in the brotowali extract was found to be approximately 0.40%, indicating a moderate level of flavonoids relative to similar medicinal plants. These results suggest that Tinospora crispa stems may serve as a potential source of natural flavonoids with therapeutic applications.